(untitled) (Tumou Tou: Jurnal Pengabdian Masyarakat, 2023)
Sinisir Village, located in Modoinding District, Minahasa Regency, is a center for horticultural crop production and an agrotourism destination. The majority of the population is involved in horticultural farming with government support through the formation of farmer groups. Even though they are productive, farmers are faced with the challenge of an uncertain climate, especially during the summer which results in water shortages and reduced crop production. To overcome this problem, an innovative solution was introduced in the form of an Internet of Things (IoT) based drip irrigation system. The method used is an active, ongoing participatory approach between the team and partners. This system allows farmers to control and monitor the condition of their plants automatically via computers connected to the internet. Via smartphones, farmers can easily monitor and control the adequacy of water and plant nutrition remotely. This system was successfully created and has been tested in the laboratory and introduced to partners through outreach and demonstration activities. The implementation of an IoT-based drip irrigation system in Sinisir Village not only increases the productivity of horticultural crops, but also provides an adaptive solution to climate change, while providing an efficient means of monitoring and control for farmers.